If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x(8x + -5) = 4x + -8 Reorder the terms: 15x(-5 + 8x) = 4x + -8 (-5 * 15x + 8x * 15x) = 4x + -8 (-75x + 120x2) = 4x + -8 Reorder the terms: -75x + 120x2 = -8 + 4x Solving -75x + 120x2 = -8 + 4x Solving for variable 'x'. Reorder the terms: 8 + -75x + -4x + 120x2 = -8 + 4x + 8 + -4x Combine like terms: -75x + -4x = -79x 8 + -79x + 120x2 = -8 + 4x + 8 + -4x Reorder the terms: 8 + -79x + 120x2 = -8 + 8 + 4x + -4x Combine like terms: -8 + 8 = 0 8 + -79x + 120x2 = 0 + 4x + -4x 8 + -79x + 120x2 = 4x + -4x Combine like terms: 4x + -4x = 0 8 + -79x + 120x2 = 0 Factor a trinomial. (1 + -8x)(8 + -15x) = 0Subproblem 1
Set the factor '(1 + -8x)' equal to zero and attempt to solve: Simplifying 1 + -8x = 0 Solving 1 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -8x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -8x = 0 + -1 -8x = 0 + -1 Combine like terms: 0 + -1 = -1 -8x = -1 Divide each side by '-8'. x = 0.125 Simplifying x = 0.125Subproblem 2
Set the factor '(8 + -15x)' equal to zero and attempt to solve: Simplifying 8 + -15x = 0 Solving 8 + -15x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -15x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -15x = 0 + -8 -15x = 0 + -8 Combine like terms: 0 + -8 = -8 -15x = -8 Divide each side by '-15'. x = 0.5333333333 Simplifying x = 0.5333333333Solution
x = {0.125, 0.5333333333}
| -x+165=90 | | y=2.82x+4.15 | | 4/3u=-16 | | 0.7/10 | | 25-2x=-4+5(5-7x) | | -(6/5)u-(3/2)=(1/5)u+7 | | 8/9x-5/9=5 | | 3(3x-4)=42 | | 36=4/3x | | 3u-(3/2)=-(1/3)u-(5/3) | | 1-y=y | | x-49=29 | | x^4/5x^2/3x^-1/2 | | 2/3x+7+3=7+x | | 30x-4=x+12 | | 5(-x-1)=-10-4x | | 7+3h=-1-5 | | 2n^2-39n-184=0 | | (7/2x)+(141/2)=(7/x)-10 | | 0.04/100 | | (x+4)(x*x-3x+2)= | | 8(3N-5)=4(5N+1) | | 7(z-5)+6z-4= | | X=y^5+31 | | 5x-(2x-12)=39 | | 2[Y+4]=3[6Y+27] | | x^2(x-y)+xy(y-x)+2y^2(y-x)= | | 2y+4y+2y+4y+7+14= | | 3x+5x-5x+4= | | 16x+12=40 | | -4(r+2)=-61 | | 15y-4y=2y-3 |